Taxonomic revision of Croton section Cleodora (Euphorbiaceae) - Caruzo, Maria Beatriz Rossi; Cordeiro, Inês (Phytotaxa, 2013)
Croton section Cleodora is a Neotropical section disjunctly distributed in Mexico and Central America, northern and northwestern South America, and eastern Brazil. Eighteen species are recognized as belonging to the section, which is characterized mainly by an arborescent or shrubby habit, presence of clear or reddish latex, leaves with a pair of basilaminar or acropetiolar glands, pistillate flowers sepals with some degree of overlap, and 4-fid or multifid styles united at the base or above, usually forming a crown. We conduct a critical revision of Croton section Cleodora, congruent with the current understanding of its evolutionary history. We provide here an identification key for the two recognized subsections (Croton subsection Sphaerogyni and C. subsection Spruceani) and their species. Descriptions, illustrations, comments about taxonomy, habitat, geographic distribution and phenological information are provided for each species. Six lectotypes are here designated.